Chimeras of Channelrhodopsin-1 and -2 from Chlamydomonas reinhardtii Exhibit Distinctive Light-induced Structural Changes from Channelrhodopsin-2 - Inaguma, Asumi (J Biol Chem, 2015)
Channelrhodopsin-2 (ChR2) from the green alga Chlamydomonas reinhardtii functions as a light-gated cation channel that has been developed as an optogenetic tool to stimulate specific nerve cells in animals and control their behavior by illumination. The molecular mechanism of ChR2 has been extensively studied by a variety of spectroscopic methods, including light-induced difference Fourier transform infrared (FTIR) spectroscopy, which is sensitive to structural changes in the protein upon light activation. An atomic structure of channelrhodopsin was recently determined by x-ray crystallography using a chimera of channelrhodopsin-1 (ChR1) and ChR2. Electrophysiological studies have shown that ChR1/ChR2 chimeras are less desensitized upon continuous illumination than native ChR2, implying that there are some structural differences between ChR2 and chimeras. In this study, we applied light-induced difference FTIR spectroscopy to ChR2 and ChR1/ChR2 chimeras to determine the molecular basis underlying these functional differences. Upon continuous illumination, ChR1/ChR2 chimeras exhibited structural changes distinct from those in ChR2. In particular, the protonation state of a glutamate residue, Glu-129 (Glu-90 in ChR2 numbering), in the ChR chimeras is not changed as dramatically as in ChR2. Moreover, using mutants stabilizing particular photointermediates as well as time-resolved measurements, we identified some differences between the major photointermediates of ChR2 and ChR1/ChR2 chimeras. Taken together, our data indicate that the gating and desensitizing processes in ChR1/ChR2 chimeras are different from those in ChR2 and that these differences should be considered in the rational design of new optogenetic tools based on channelrhodopsins.